GROUNDING FOR EFFECTIVE TECHNOLOGY OF REPROCESSING COARSE GRAINED SCREENINGS FROM CRUSHING AND SCREENING PLANTS OF KRYVYI RIH BASIN - Demchenko, O.; Evtekhov, V.; Evtekhova, A.; Georgiieva, H. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The high–grade iron ores of Kryvyi Rih basin are among the most thoroughly studied geological objects of banded iron formation. High–grade hematite ores deposits are exploited by seven mines and two open–pits. The average iron content in ores is 55–58 mass %. Because of the complexity of ore bodies contacts and imperfection of ore mining technology, nonmetallic components enter the ore mass in the process of its extraction from the interior. This explains the lower content of iron (52–54 mass %) in extracted ore mass compared to its average content in the ores prepared for mining. In order to increase the iron content in saleable ore up to 55–60 mass %, crushing and screening plants (CSP) operate at all Kryvbass mines, using the method of three–stage crushing and screening to separate less stable particles of high–grade ores and harder particles of most low–iron rocks. The processing waste represents a coarse–grained screening of the CSP (particle size 20–100 mm) with a total iron content of 39 to 46 mass %, about 43 mass % on average. The goal of the work was to analyze the data of previously performed mineralogical and technological studies, to determine the reason for the non–optimality of the results obtained earlier; to justify mineralogically the effective technology for the production of high–quality sinter ore and concentrate from CSP screening. On the basis of petrographic and mineralogical studies carried out by the authors, methods of magnetic and gravitational beneficiation of the material crushed to the optimum size were chosen. According to the obtained data, the production of the following useful final products with different iron content is possible from the screenings of CSP: ordinary sinter ore (iron content 55–59 mass %), high–quality sinter ore (60–62 mass%); sinter concentrate (63–64 mass %); ordinary concentrate (65–67 mass %); high–quality concentrate (68–69 mass %). The products quality depends on the particle size in the grinding products, which varies from 1–2 mm (ordinary sinter) to less than 0.1 mm (high–quality concentrate). Comparison of different methods of beneficiating crushed material showed the most effective method to be the gravitational one. The scientific novelty of the work consists in the mineralogical substantiation of the technology of the production of high-quality useful end products from the dumping of the CSP screenings at the Kryvbas mines. The practical significance of the work is justification for the possibility of producing additional volumes of high–quality sinter ore and concentrate, reducing storage of processing waste.
Keywords: banded iron formation; Kryvyi Rih basin; high–grade iron ores; processing waste; reuse of ore processing waste